Le sermon comme manuductio chez Nicolas de Cues - Counet, Jean-Michel (Revue des sciences philosophiques et théologiques, 2014)
After having delivered some general information regarding the corpus of Nicholas of Cusa’ Sermons, the article focuses on the concept of manuductio (the act of taking by the hand). Drawn from the dionysian tradition, it is for the Cusan an important notion. The human intellect discovers only gradually the most elevated realities, for which it needs an experimented guide to induct him into the practice of contemplation. The art of Conjectures, the teaching of the De Visione Dei, the Trinitarian developments of the Cribratio Alkorani are presented by Nicolas as manuductiones. We will show here that the sermon is indeed conceived by the Cusan as a manuductio in faith leading the faithful to a deeper understanding of being and acting in Christ. Philosophy plays a limited but real role in this itinerary toward the intelligence of faith.